Structural systems of buildings of the polytechnic museums - D A Chistyakov (RUDN Journal of Engineering Research, 2014)
The article is devoted to the study of structural systems used for coating of buildings of the Polytechnic museums and revealing of tendencies of their application for subsequent design.